(untitled) (Bangladesh Heart Journal, 2023)
This prospective study was designed to determine the incidence of pulmonary complications after open cardiac surgery as well as to identity predisposing factors of these complications at NICVD, Dhaka, Bangladesh. The cumulative incidence of pulmonary complications after open heart surgery was 16.85% (15of 89) with a mortality rate of 33.33% (5 of 15) and the overall mortality among all patients was 5.62% (5 of 89). Pulmonary complications occurred in 15.9% of patients with coronary artery revascularization, 11.53% in patients with valvular replacement and 26.31% in patients with congenital heart disease. ARDS occurred in 2.25% of patients with a mortality rate of about 100%, pneumonia in 5.62%, atelectasis in 2.25%, pleural effusion in 5.62% and pneumothorax in 3.37%. The most predisposing factors were massive blood transfusion, re-exploration for control of post-operative bleeding, cardiopulmonary resuscitation and prolonged length stay in the intensive care unit. Bangladesh Heart Journal 2023; 38(1): 8-12